2017
DOI: 10.17979/reipe.2017.0.13.2105
|View full text |Cite
|
Sign up to set email alerts
|

Entornos hipermedia: posibilidades y retos

Abstract: ResumenDiversos estudios subrayan el potencial que los entornos hipermedia tienen para el aprendizaje, sin embargo, las intervenciones demuestran desiguales resultados en función del tipo de aprendiz, contexto y características del entorno del entorno de aprendizaje. En el presente trabajo se sintetizan los resultados de una revisión sistemática de los artículos científicos sobre entornos hipermedia indexados en la Web of Science. Los resultados ponen de relieve la amplia utilización de este tipo de recursos e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…These results seem to show that the postulates that gave rise to the creation and implementation of the EHEA, particularly the ECTS system of credits, have not yet been interiorized by students, who continue to perceive their study more traditionally. It is necessary to continue improving effective interventions regarding learning self-regulation; in this sense training programs in higher education such eTRAL (Cerezo et al, 2017) or Metatutor (Bouchet et al, 2016) have shown to have positive impacts on academic performance and success (Esteban et al, 2017) and can encourage better fit between students’ characteristics and the requirements from EHEA based study plans.…”
Section: Resultsmentioning
confidence: 99%
“…These results seem to show that the postulates that gave rise to the creation and implementation of the EHEA, particularly the ECTS system of credits, have not yet been interiorized by students, who continue to perceive their study more traditionally. It is necessary to continue improving effective interventions regarding learning self-regulation; in this sense training programs in higher education such eTRAL (Cerezo et al, 2017) or Metatutor (Bouchet et al, 2016) have shown to have positive impacts on academic performance and success (Esteban et al, 2017) and can encourage better fit between students’ characteristics and the requirements from EHEA based study plans.…”
Section: Resultsmentioning
confidence: 99%